Cancer-associated fibroblasts in ovarian cancer: research progress - Yuance Xu; Danting Sun; Junqi He; Qin Yao (Frontiers in Oncology)
Ovarian cancer, known for its high invasiveness and therapeutic resistance, is one of the leading causes of death from gynecological tumors. The tumor microenvironment (TME) plays a crucial role in the development of ovarian cancer, with cancer-associated fibroblasts (CAFs) being a key non-tumor cell component. They significantly affect the prognosis of ovarian cancer by promoting tumor cell proliferation, invasion, metastasis, immune evasion, and drug resistance. The heterogeneity of CAFs provides a new perspective for targeted therapy in ovarian cancer. This review comprehensively analyzes the mechanisms of action, heterogeneity characteristics, and role in the immune microenvironment of CAFs in ovarian cancer, and discusses targeted therapy strategies for CAFs, aiming to provide new theoretical basis and treatment directions for the treatment of ovarian cancer.